2016
DOI: 10.3171/2015.10.peds14443
|View full text |Cite
|
Sign up to set email alerts
|

Leksell Gamma Knife treatment for pilocytic astrocytomas: long-term results

Abstract: OBJECTIVE The purpose of this study was to evaluate long-term treatment results, radiation-related toxicity, and prognostic factors for the progression-free survival (PFS) of patients with pilocytic astrocytomas treated by means of stereotactic radiosurgery with a Leksell Gamma Knife. METHODS A total of 25 patients with pilocytic astrocytomas underwent Gamma Knife surgery during the period 1992–2002. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…Simonova et al [ 44 ] assessed long-term outcomes with GK-based stereotactic irradiation for PA. Their series included 25 pediatric patients with a median age of 13 years (range: 3-17 years). Median target volume was 2.7 cc (range: 0.2-25 cc).…”
Section: Radiosurgery For Pamentioning
confidence: 99%
See 1 more Smart Citation
“…Simonova et al [ 44 ] assessed long-term outcomes with GK-based stereotactic irradiation for PA. Their series included 25 pediatric patients with a median age of 13 years (range: 3-17 years). Median target volume was 2.7 cc (range: 0.2-25 cc).…”
Section: Radiosurgery For Pamentioning
confidence: 99%
“…Patients with a planning target volume of 2.7 cc or less had increased PFS. Authors concluded that radiosurgery offers an alternative treatment modality, providing long term local control for management of small residual or recurrent PAs[ 44 ].…”
Section: Radiosurgery For Pamentioning
confidence: 99%
“…treatments, but the majority are single‐session radiosurgery procedures. Complication rates are low and consist mainly of transient radiation‐induced edema 1‐5 and reversible enlargement of tumor‐associated cysts 2 . Radiosurgery in the un‐resected population may be supported by the lower integral dose delivered to the brain using conventional intensity‐modulated radiation therapy (IMRT)‐based conformal therapy 6 …”
Section: Radiosurgerymentioning
confidence: 99%
“…Эффективность СРХ, по мнению большинства авторов, не вызывает сомнений. Однако на данный момент публикации о проведении СРХ по поводу ПА немногочисленны, а количество наблюдений в этих работах невелико [10][11][12][13][14][15][16][17].…”
Section: Introductionunclassified